PHYSICO-CHEMICAL CHARACTERIZATION OF SPRING AND SALT LAKES FROM SOMESENI TURENI (CLUJ COUNTY) - BRASOVAN, Andreea; CÂMPEAN, Ramona Flavia; OLAH, Neli Kinga; MORGOVAN, Claudiu; POPESCU, Carmen; ATYIM, Paul (Studia Universitatis Babeș-Bolyai Chemia, 2015)
The study refers to the analysis of the chemical composition of water samples from Pata Rât salt lake and salty spring from Micești. The physical and mineralogical characteristics of water and sludge specific of Pata Rât lake are suitable to be used in alternative treatments for rheumatism, skin peeling treatments and skin SPA therapy. The difference in salt crystallization in homogeneous and heterogeneous conditions was evaluated by using a model of salt crystallization in homogeneous conditions. The optical mineralogical micro-photographs in polarized light of the water samples are providing information about heterogeneous crystallization of salt. The mineralogical composition of the water sample was determined by X-ray diffraction and the following minerals were determined: quartz, calcite, lepidolite and kaolinite. By colorimetry were determined the physico-chemical properties of salty water. It was determined also the pH and the conductivity.